Linezolid Susceptibility And Potential Resistance Mechanisms Among Mrsa Isolated From Two Major Public Hospitals In Malaysia - Thiruchelvi , Pulingam (2014)
Linezolid is the first antibiotic of a new structural class, the oxazolidinones, to be approved for clinical use in 35 years. This antimicrobial agent is broadly effective against drug-resistant gram-positive pathogens which commonly cause infections. Linezolid merupakan antibiotik pertama dari kelas struktur baru, oksazolidinon, yang telah diluluskan untuk kegunaan klinikal setelah 35 tahun. Ejen anti-mikrob ini berkesan secara meluas terhadap patogen gram-positif rintang-antibiotik yang sering menjadi punca jangkitan bakteria.